Transnational trafficking, law enforcement and victim protection: A middleman trafficker's perspective - Randall K. Q. Akee; Arjun S. Bedi; Arnab K. Basu; Nancy Chau (Institute for the Study of Labor (IZA), 2011)
We explore three hitherto poorly understood characteristics of the human trafficking market - the cross-border ease of mobility of traffickers, the relative bargaining strength of traffickers and final buyers, and the elasticity of buyers' demand. In a model of two-way bargaining, the exact configuration of these characteristics is shown to determine whether domestic and foreign crackdowns on illicit employment mutually reinforce or counteract one another in efforts to stem the tide of trafficking. Estimation results from a gravity model of trafficking present evidence consistent with the mutual reinforcement view, indicating considerable ease of mobility, partial bargaining power, and inelastic demand.
urn:nbn:de:101:1-201201114018
Keywords: K42; R23; O15; 330; human trafficking; two-way Nash bargaining; victim protection; law enforcement; Menschenhandel; Grenze; Internationale Arbeitsmobilität; Schwarzarbeit; Arbeitsnachfrage; Verhandlungsmacht; Theorie; Schätzung; USA